PENGARUH METODE PEMBELAJARAN PEER TEACHING TERHADAP KEMAMPUAN TEKNIK PASSING BAWAH PADA PEMBELAJARAN BOLA VOLI KELAS X SMAN 1 BUNGURSARI - Febriyanti Cahyaningtias; Rhama Nurwansyah Sumarsono; Ardawi Sumarno; Irfan Zinat Achmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aimed to examine the effect of the Peer Teaching model on the development of the underhand pass technique in volleyball for students at SMAN 1 Bungursari. Employing a quantitative approach with an experimental design utilizing a one-group pretest-posttest model, the research involved the X-2 class, consisting of 45 respondents, who were selected using the Total Sampling technique. Descriptive results indicated a significant increase in the volleyball underhand passing ability, evidenced by the mean score rising from 59 in the pretest to 76 in the posttest. Hypothesis testing, performed using the Paired Samples T Test, yielded a significance level of 0.000, which is less than the standard threshold of 0.05. This result confirms a statistically significant influence between the administered treatment and the learning outcomes. Therefore, it is concluded that the Peer Teaching learning method is proven effective in enhancing the underhand passing ability in volleyball among tenth grade students at SMAN 1 Bungursari.